Analysis of integrated avian RNA tumor virus DNA in transformed chicken, duck and quail fibroblasts. - Sabran, J L (1979)
The state of integration of avian sarcoma virus DNA in the genomes of transformed chicken, duck, and quail fibroblasts was deduced by means of restriction enzyme digestion of total cell DNA, gel electrophoresis, and subsequent analysis by the procedure of Southern. The cells used in these studies were either mass-infected cultures or clones of infected cells selected by their ability to form colonies in agar. For both mass-infected cultures and clones of cells of all three species, we found that integration occurred at a specific site on the viral genome but appeared to occur at many sites on the cell genome. At least some of the integrated viral DNA existed as intact nonpermuted species flanked by direct terminal repeats of at least 0.134 megadalton (217 base pairs). For each of 12 transformed quail clones studied, it was possible to detect, after digestion with Kpn I, unique junctions between viral and cellular DNA. That is, at our level of analysis, the integration site on the cell genome for each clone was different. However, within each of the 17 chicken and 9 duck clones of transformed cells, a heterogeneity presumably occurred during the outgrowth of the cell clone population, in that we could not readily detect identifiable cell-virus junction fragments.